8h+(-15h)+(-5)=(-19)

Simple and best practice solution for 8h+(-15h)+(-5)=(-19) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8h+(-15h)+(-5)=(-19) equation:


Simplifying
8h + (-15h) + (-5) = (-19)
8h + (-15h) + -5 = (-19)

Reorder the terms:
-5 + 8h + (-15h) = (-19)

Combine like terms: 8h + (-15h) = -7h
-5 + -7h = (-19)
-5 + -7h = -19

Solving
-5 + -7h = -19

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + -7h = -19 + 5

Combine like terms: -5 + 5 = 0
0 + -7h = -19 + 5
-7h = -19 + 5

Combine like terms: -19 + 5 = -14
-7h = -14

Divide each side by '-7'.
h = 2

Simplifying
h = 2

See similar equations:

| 9+2x=15-3x | | 7(9+2x)=15-3x | | 4(c+2)=16 | | 4x/(x+2)=2 | | -(x)-6/2=15 | | 2j-3j+19=2 | | -12+n=1 | | x+9=5(2x+8) | | 80.75/z5 | | 7(9+-2x)=-33-7x | | x^2-7=4x-11 | | 1/9x^2-1=-3/4 | | 7(9+-2x)=3(5x-2) | | 4x+(4-x)-5=2x+3 | | 2(24-y)+2y=48 | | z=11+3(x+y)findx | | 7(9+-2x)=9(5x-2) | | 7(9+-2x)=9(7-2x) | | 8(100-k)+10k=840 | | 7(9+-2x)=9(7x-2) | | 16x^2-11x+26=0 | | 9c-36= | | (x+y)dx+(x-y)dy=0 | | 7(5-4)+3x=4(x+2) | | -13-7x=9x-11 | | 12x+7=-4x+9 | | -15=-5y | | 8x+4/2=4x-2/3 | | 15/3-7x=9+5x | | 27-6d=7+4 | | 57/9+48/9 | | 15-10=6x-(x+2)+(-x+3) |

Equations solver categories